Textbook of medical psychiatry - Summergrad, Paul; Silbersweig, David; Muskin, Philip R.; Querques, John, 1970- (American Psychiatric Association Publishing, 2020)
"The Textbook of Medical Psychiatry focuses on medical disorders that can directly cause or affect the clinical presentation and course of psychiatric disorders. Clinicians who work primarily in psychiatric settings, as well as those who practice in medical settings but who have patients with co-occurring medical and psychiatric illnesses or symptoms, can benefit from a careful consideration of the medical causes of psychiatric illnesses. The editors, authorities in the field, have taken great care both in selecting the book's contributors, who are content and clinical experts, and in structuring the book for maximum learning and usefulness. The first section presents a review of approaches to diagnosis, including medical, neurological, imaging, and laboratory examination and testing. The second section provides a tour of medical disorders that can cause psychiatric symptoms or disorders, organized by medical disease category. The third section adopts the same format as the second, offering a review of psychiatric disorders that can be caused or exacerbated by medical disorders, organized by psychiatric disorder types. The final section contains chapters on conditions that fall at the boundary between medicine and psychiatry. Even veteran clinicians may find it challenging to diagnose and treat patients who have co-occurring medical and psychiatric disorders or symptoms. The comprehensive knowledge base and clinical wisdom contained in the Textbook of Medical Psychiatry makes it the go-to resource for evaluating and managing these difficult cases"--